Long‐term observation in patients with esophageal varices after endoscopic variceal ligation accompanied with 24‐hour pH monitoring. Issue 11 (10th September 2020) - Hidaka, Hisashi; Tanabe, Satoshi; Uojima, Haruki; Shao, Xue; Iwasaki, Shuichiro; Wada, Naohisa; Kubota, Kousuke; Tanaka, Yoshiaki; Nakazawa, Takahide; Shibuya, Akitaka; Kokubu, Shigehiro; Koizumi, Wasaburo
Abstract : Aim: Esophageal variceal ligation (EVL) is usually carried out to decrease the risk of hemorrhage. Several complications have been reported with the procedure, including bleeding from ligation‐induced esophageal ulcers or heartburn. However, there is scant evidence for gastroesophageal reflux caused by EVL. The aim of this study was to assess 24‐h pH monitoring in the esophagogastric junction before and after EVL and the bleeding rate for 18 months. Methods: We undertook this single‐center prospective trial in Kitasato University Hospital (Sagamihara, Japan). We included patients with cirrhosis who were Child–Pugh classification A or B, without uncontrollable hepatocellular carcinoma, and had F2 or larger esophageal varices, and/or were red color sign (RC) positive. The study period was from July 2012 through September 2017 for 32 patients enrolled in this study and followed up until March 2019. Results: Baseline characteristics were: median Child–Pugh score, 6; and mean age, 64.3 years. Before and after EVL, the median 24‐h under pH 4 holding time percentages of all patients were 0.6% (range, 0–5.6%) and 0.95% (range, 0–50.6%), respectively, without a significant difference ( P  = 0.107). We could not find any G3 or G4 adverse events during this study, and 75% of the patients who had already suffered from moderate gastroesophageal reflux became worse after EVL ( P  = 0.18) and required antacid therapies. There were no patients with hemorrhage from esophageal varices. Conclusions: Esophageal variceal ligation for esophageal varices did not significantly change gastroesophageal reflux. Therefore, acid suppressive therapy might be unnecessary for patients who do not suffer from gastroesophageal reflux after EVL.